Technik- und Wissenschaftsgeschichte in der universitären Lehre. Formate, Adressaten, Konzepte - Popplow, Marcus [Hrsg.] (Technikdiskurse : Karlsruher Studien zur Technikgeschichte / Hrsg.: Karlsruher Institut für Technologie (KIT), Institut für Technikzukünfte, Teilinstitut für Geschichte, 2019)
This edited volume, for the first time, presents examples for three categories of university courses in teaching the history of technology and science: introductory courses, object-oriented teaching and interdisciplinary teaching. The resulting overview encourages to experiment with new formats in teaching the history of technology and science, to foster exchange on such efforts and, not the least, to more comprehensively appreciate engagement in university teaching.